EXPLORING FRONTIERS AT THE UNITED STATES-MEXICO BORDER: HEALTH LITERACY COMMUNICATION IN THE U.S.-MEXICO BORDER REGION OF NEW MEXICO AND COORDINATING THE SUMMER 2012 FRONTIER PROGRAM FIELD TRIP IN LAS CRUCES, NEW MEXICO - Engel, Jennifer (My University, 2015)
The New Mexico Department of Health (NM DOH) Office of Border Health in Las Cruces, New Mexico, conducted a survey in the summer months of 2012 concerning information about access to healthcare within the Hispanic population in their jurisdiction. The NM DOH Office of Border Health was interested in directing their resources to improve outreach to the Hispanic population that they serve. During my internship with the NM DOH Office of Border Health I contributed to this project. I created a survey instrument, aided in its translation to Spanish, compiled “goody bags” to use as incentives and distribute to participants, conducted the survey in various locations in Doña Ana County, input data into the Epi InfoTM computer program used at the NM DOH Office of Border Health, and helped to interpret results. The second part of my field experience culminated during the week of Monday, June 18, 2012 through Saturday, June 23, 2012, when the Frontier Program hosted an experiential learning field trip that brought students, faculty and staff from different universities across the United States to the Las Cruces, New Mexico area and the Santa Teresa Border Crossing. I assisted the Frontier Program Coordinator in Las Cruces, New Mexico, with planning the logistical aspects of the portion of the field trip in Las Cruces through visiting locations and meeting with key people at the Santa Teresa Border Crossing, J.H. Rose Logistics, LLC, New Mexico State University, and at La Posta de Mesilla historic Mexican restaurant. This report summarizes my experiences working with both the NM DOH Office of Border Health and the Frontier Program while in Las Cruces, New Mexico. I also outline, provide, and explain the materials created for each of these projects.
Keywords: Border health; Frontier program; Public Health (0573)